Damage due to start-stop cycles of turbine runners under high-cycle fatigue. (December 2021) - Savin, O.; Baroth, J.; Badina, C.; Charbonnier, S.; Bérenguer, C.
Abstract: This study presents a strategy to estimate the extra cost due to start-up and shut-down of hydro turbines under high-cycle fatigue. The principle is to compare estimations of cumulated damages from three elementary sequences representing steady and transient regimes (start and stop cycles) of turbine runners, from in-situ strain measurements. Rainflow cycle-counting is used to extract stress cycles from these three sequences. Fatigue design curves are defined, taking into account design codes, laboratory tests and a probabilistic approach. The analysis of these curves, coupled with the Palmgren-Miner rule, allows estimating damage ratio, i.e. extra costs of start and stop events, through an equivalent number of normal operating hours. This approach is applied to Francis and Pelton runners. Different results are discussed in terms of damage distributions and extra costs of start and stops.